(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2022)
The history of India-Pakistan relations has been brimming with squabbles and conflicts since their separation in 1947. Except for the significant and lasting Indus Waters Treaty (IWT) of 1960 for sharing river waters, little-to-none economic cooperation has taken place between the two riparian states. This paper analyses some noticeable gaps that have rendered this treaty obsolete such as the escalating influence of climatic changes on water resources of the region and some other shortcomings, namely the possible limits of shared water usage, unrestricted use of shared waters for power generation, rerouting of water, and the lack of synergistic projects. Moreover, due to the exponential increase in water and energy demand along with the aggravating depletion of water tables in Pakistan, the treaty is failing to secure the combined water resources of the Indus river basin. This study presents the policy perspective to guide future endeavours, ensuring the treaty’s survival as it needs the necessary adjustments to enhance the socio-economic cooperation between India and Pakistan, put in place the collective efforts for mitigation of risks posed by climate-induced disasters, and improve the management of water resources for collaborative development.